Kajian terhadap penggunaan IBS dalam projek swasta di kawasan Lembah Klang - Mohd Nawi Mohd Nasrun, Azhari Azman Mohamed Nor, Mohamad Kamar Kamarul Anuar, Abd Hamid Zuhairi, (N/A, 2013)
Kajian terhadap penggunaan IBS dalam projek swasta di kawasan Lembah Klang by Mohd Nawi Mohd Nasrun, Azhari Azman Mohamed Nor, Mohamad Kamar Kamarul Anuar, Abd Hamid Zuhairi,